Characterization of my18, a mutant exhibiting abnormal expression of the C. elegans polycystic kidney disease gene - Mansukhani, Neel (My University, 2007)
Autosomal Dominant Polycystic Kidney Disease (ADPKD) is a common genetic disorder affecting 1/400 to 1/800 individuals in the population. Mutations in the human genes PKD1 and PKD2, which encode Polycystin-l (PC-I) and Polycystin-2 (PC-2), respectively, account for 95% of ADPKD cases. Defects in sensory receptor localization in cilia, or cilia formation may contribute to many human diseases including ADPKD. The nematode Caenorhabditis elegans uses sensory cilia localized to the end ofsensory neurons to perceive environmental stimuli. Sensory information is integrated and used to determine appropriate behavioral responses. The C. elegans ADPKD gene homologs lov1/PC-l and pkd-2/PC-2 localize and function in male specific sensory cilia, and are required for proper male mating behavior. A pilot mutagenesis screen isolated 21 separate mutations affecting PKD-2 ciliary localization, which were grouped into three categories. This research was done on my18, a nlutation which effects PKD-2 expression at the transcription level. In a subset ofmy18 males, tail fan formation is defective, which maybe responsible for defects in male mating behavior. Furthermore, in my18 males with normal tail fan formation mating behavior and efficiency was compromised compared to wild type. Linkage analysis mapped my18 to chromosome IV, and further mapping experiments are in progress.
18 p.
Keywords: Genetics